Laporan Pembangunan Dunia 2005. Iklim Investasi yang Lebih Baik bagi Setiap Orang - [Tidak Terdaftar] (Salemba Empat, 2005)
Laporan Pembangunan Dunia 2005. Iklim Investasi yang Lebih Baik bagi Setiap Orang